Disaster preparedness in the hills: Natural hazard modeling using GIS and remote sensing - Oberoi S.V.; Thakur N.K. (My University, 2025)
Spatial and temporal multi-layered information is required to assess the natural hazard susceptibility in the mountainous regions. The manual method of data integration for targeting potential zones susceptible to these hazards is expensive and time-consuming. The aim of this study is to operationalise a working methodology wherein geo-environmental parameters are analysed to develop models for mapping avalanche and landslide-prone areas using remotely sensed data and Geographic Information System (GIS). This technique can be used for speedy generation and updating of the landslide/avalanche hazard maps of remote areas and strategically plan for the future developmental activities by delineating the potential zones and avoiding them while laying out new roads in this difficult terrain. The utility of this methodology for the collection, integration and analysis of spatially-oriented data, as well as in finding out the inherent relation between separate entities has also been highlighted for an existing hill road in the Manali-Leh Axis situated in the Lower and Upper Himalayan snow climatic zone. It is expected that the present paper will highlight the utility of temporal remotely-sensed data and knowledge-based Geographical Information Systems for collection, integration and analysis of spatially-oriented data, as well as in finding out the inherent relation between separate entities.